Development Of Mathematics Learning Media Smart Snakes and Ladder Statistics (UTAPTIK) In Primary School Statistics Materials - Heriyanti, Lutfiah; Pranata, Khavisa (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
Learning media is an important element in the learning process, functioning as a valuable instrument for transmitting knowledge. The learning media used in education must be appropriate to the needs and characteristics of students. In class 6 at SDN Pasirangin 05 the majority of students are actively involved in the learning process. Therefore, it is very appropriate to utilize learning media that fosters innovation, fun, and increases students' understanding of the subject matter. The objectives of this research are: (1) Designing and constructing UTAPTIK learning teaching materials. (2) What is the level of validity of the UTAPTIK media used in learning mathematical statistics concepts? (3) Knowing students' responses to UTAPTIK game media. Researchers used Research and Development methodology to conduct research. This research methodology uses the ADDIE development paradigm, namely the Analyze, Design, Development, Implement and Evaluate stages. This research uses data collection methodology such as filling out questionnaires, making observations, and documenting findings. This research resulted in the development of UTAPTIK learning media which consists of several components such as a game arena, dice, game guide book, and statistics cards. The results of this research are UTAPTIK products with product validation results showing very valid criteria determined by a score of 97% from material expert validators. In addition, the criteria were considered valid with a score of 76% from media expert validators. The validation results by material expert validators and media expert validators are classified as very valid so that the media can be tested. The student questionnaire obtained a score of 94% in the very valid category. The smart statistical snakes and ladders game media (UTAPTIK) is classified as very valid and worthy of being integrated into the learning process of class VI students.